Design of a Cryogenic Duplex Pressure-Swirl Atomizer through CFDs for the Cold Conservation of Marine Products - Ayala, Eduardo (2023)
The following article proposes the design of a bi-centrifugal atomizer that allows the interaction of sprays from two fluids (water and liquid nitrogen). The liquid nitrogen (LN2) is below −195.8 °C, a temperature low enough for the nitrogen, upon contact with the atomized water, to cause heat loss and bring it to its freezing point. The objective is to convert the water droplets present in the spray into ice. Upon falling, the ice particles can be dispersed, covering the largest possible area of the seafood products intended for cold preservation. All these phenomena related to the interaction of two fluids and heat exchange are due to the bi-centrifugal atomizer, which positions the two centrifugal atomizers concentrically, resulting in the inevitable collision of the two sprays. Each of these atomizers will be designed using a mathematical model and CFDs tools. The latter will provide a better study of the flow behavior of both fluids inside and outside the bi-centrifugal atomizer. Hence, the objective revolves around confirming the validity of the mathematical model through a comparison with numerical simulation data. This comparison establishes a strong correlation (with a maximum variance of 1.94% for the water atomizer and 10% for the LN2 atomizer), thereby ensuring precise manufacturing specifications for the atomizers. It is important to highlight that, in order to achieve the enhanced resolution and comprehension of the fluid both inside and outside the duplex atomizer, two types of meshes were utilized, ensuring the utilization of the optimal option. Similarly, the aforementioned meshes were generated using two distinct software platforms, namely ANSYS Meshing (tetrahedral mesh) and ANSYS ICEM (hexahedral mesh), to facilitate a comparative analysis of the mesh quality obtained. This comprehension facilitated the observation of water temperature during its interaction with liquid nitrogen, ultimately ensuring the freezing of water droplets at the atomizer’s outlet. This objective aligns seamlessly with the primary goal of this study, which revolves around the preservation of seafood products through cold techniques. This particular attribute holds potential for various applications, including cooling processes for food products.